Learning and Wage Dynamics - Farber, H. S.; Gibbons, R. (Quarterly Journal of Economics, 1996)
We develop a dynamic model of learning about worker ability in a competitive labor market. The model produces three testable implications regarding wage dynamics: (1) although the role of schooling in the labor market's inference process declines as performance observations accumulate, the estimated effect of schooling on the level of wages is independent of labor-market experience; (2) timeinvariant variables correlated with ability but unobserved by employers ( such as certain test scores) are increasingly correlated with wages as experience increases; and (3) wage residuals are a martingale. We present evidence from the NLSY that is broadly consistent with the model's predictions.